Cybersex addiction: an overview of the development and treatment of a newly emerging disorder (Medical Journal of Indonesia, 2020)
Cybersex addiction is a non-substance related addiction that involves online sexual activity on the internet. Nowadays, various kinds of things related to sex or pornography are easily accessible through internet media. In Indonesia, sexuality is usually assumed taboo but most young people have been exposed to pornography. It can lead to an addiction with many negative effects on users, such as relationships, money, and psychiatric problems like major depression and anxiety disorders. A few instruments may be used to detect cybersex behavior. This review was aimed to provide a comprehensive discussion about cybersex addiction in Indonesian society and the importance of its screening for this condition to enable its early detection and subsequent management.